(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
In This paper, a single pole broken spike shaped antenna is there. The main objective is for the application of WiMAX band. For the required band, we carried out the proposed antenna into different iteration models. The proposed antenna which is heart shape works in WiMAX Frequency (3.2GHz-4,1GHz). To Increase the band width(900MHz), and gain (3dB), A two Slotted ring resonator in heart shape is done in them last iteration. In this design the parameters like VSWR is almost less than the WiMAX band and impedance will be 89% has been noted. Finallly the monopole antenna which in broken heart shape works at WiMAX band having medium gain, high efficiency, reduce in size that are useful for WiMAX band applications